Toxicity problems with ammoniated dry roughages - D. Simms; Gerry L. Kuhl; J. Brethour (Kansas Agricultural Experiment Station Research Reports, 1984)
In two trials conducted at the Fort Hays Experiment Station, symptoms of toxicity (hyperexcitability, circling, convulsions, death) were observed in several newborn calves (l to 14 days of age) nursing cows consuming ammoniated forage sorghum hay. None of these symptoms was observed in calves nursing cows consuming untreated hay. No toxicity symptoms were observed in the cows on any treatment. However, several instances of similar symptoms in cattle consuming ammoniated forages have been reported in growing calves and adult cattle in Kansas, Texas, California, and Kentucky. The primary forages involved in these incidents were forage sorghum, hybrid sudan, cereal grain, brome, and fescue hays. To date, no problems have been reported with ammoniated wheat straw or other Poor quality forages. Analyses of the treated forages associated with several of these toxicity incidents have shown relatively high levels of imidazole compounds-chemicals with convulsive properties previously implicated in toxicity with ammoniated molasses.
Keywords: Cattlemen& #x27; s Day; 1984; Kansas Agricultural Experiment Station contribution; no. 84-300-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 448; Beef; Toxicity; Ammonia; Roughages